An heiress's guide to deception and desire - Collins, Manda (Forever, 2021)
"After Caroline's dear friend is kidnapped ... she has no choice but to work with Lord Valentine Thorn, the same man who broke her heart. Worse, when her actions put her father's business at risk, a marriage of convenience may be her only solution ... Val, the new Viscount Wrackham is in an untenable position: His father is demanding he find a respectable bride to secure the succession. Yet the only woman he's ever loved, Miss Caroline Hardcastle, is notorious for behaving improperly"--